Application of Immune Infiltration Signature and Machine Learning Model in the Differential Diagnosis and Prognosis of Bone-Related Malignancies - Li, Guo-Qi; Wang, Yi-Kai; Zhou, Hao; Jin, Lin-Guang; Wang, Chun-Yu; Albahde, Mugahed; Wu, Yan; Li, Heng-Yuan; Zhang, Wen-Kan; Li, Bing-Hao; Ye, Zhao-Ming (Frontiers in Cell and Developmental Biology, 2021)
Bone related malignancies, such as osteosarcoma, Ewing's sarcoma, multiple myeloma, and cancer bone metastatic have similar histological context, but they are distinct in origin and biological behavior. We hypothesize that a distinct immune infiltrative microenvironment exists in these four most common malignant bone-associated tumors and can be used for tumor diagnosis and patient prognosis. After sample cleaning, data integration, and batch effect removal, we used 22 publicly available datasets to draw out the tumor immune microenvironment using the ssGSEA algorithm. The diagnostic model was developed using the Random Forest. And further statistical analysis of the immune microenvironment and clinical data of patients with osteosarcoma and Ewing's sarcoma was carried out. The results suggested significant differences in the microenvironment of bone-related tumors, and the diagnostic accuracy of the model was higher than 97%. Also, the high infiltration of multiple immune cells in Ewing’s sarcoma was suggestive of poor patient prognosis. Meanwhile, increased infiltration of macrophages and B cells suggested a better prognosis for patients with osteosarcoma, and Effector Memory CD8 T cells and Type 2 T helper cells correlated with patients' chemotherapy responsiveness and tumor metastasis. Our study revealed that the random forest diagnostic model based on immune infiltration can accurately perform the differential diagnosis of bone-related malignancies. The immune microenvironment of osteosarcoma and Ewing's sarcoma has an important impact on patient prognosis. Suppressing the highly inflammatory environment of Ewing's sarcoma and promoting macrophage and B-cell infiltration may have good potential to be a novel adjuvant treatment option for osteosarcoma and Ewing's sarcoma.